Biofortification of oil quality, yield, and nutrient uptake in Indian mustard (Brassica juncea L.) by foliar application of boron and nitrogen - Dhaliwal, Salwinder Singh; Sharma, Vivek; Shukla, Arvind Kumar; Kaur, Manmeet; Verma, Vibha; Sandhu, Prabhjodh Singh; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Hossain, Akbar (Frontiers in Plant Science, 2022)
Indian mustard (Brassica juncea L.) is an essential oilseed crop that offers important nutrients to human beings. However, the concurrent micronutrient deficiencies including boron (B), sulfur (S), and nitrogen (N) could pose a significant threat to public health. Therefore, this study was conducted at the Punjab Agricultural University, Ludhiana, with nine treatments, i.e., T1-Control (recommended NPK only), T2- borax (0.5%) at flowering, T3-borax (1.0%) at flowering,T4- borax (0.5%) + urea (1.0%) at flowering,T5-borax (1.0%) + urea (1.0%) at flowering, T6-borax (0.5%) at flowering + capsule formation, T7-borax (1.0%) at flowering + capsule formation, T8-borax (0.5%) + urea (1.0%) at flowering + capsule formation, T9-borax (1.0%) + urea (1.0%) at flowering + Capsule formation, replicated three times in a randomized block design for 2 years (2020–2021 and 2021–2022). The foliar application of borax (1.0%) + urea (1.0%) at the flowering and capsule formation stage (treatment T9) was highly efficient in increasing food quality parameters such as crude fiber, total soluble solids (TSS), and protein content with maximum values of 3.77, 24.9, and 27.53%, respectively. Also, maximum yields of seed as well as stover for treatment T9 were 1.376 and 6.625 kg ha−1, respectively. Similarly, the results for B, S, and N concentrations in seed (27.71 mg kg−1, 17.69 mg kg−1, and 2.35%), as well as stover (25.92 mg kg−1, 17.31 mg kg−1, and 0.33%), were maximum in treatment T9. Also, B, S, and N uptake by seed (38.18 g ha−1, 24.40 g ha−1, and 32.05 Kg ha−1) and stover (172.55 g ha−1, 115.44 g ha−1, and 21.99 Kg ha−1) were maximum for the treatment T9 involving borax (1.0%) + urea (1.0%) at the flowering and capsule formation stage. Whereas, the concentration and uptake decreased in the treatments involving the sole application of borax and urea. Therefore, the application of borax (1.0%) and urea (1.0%) at the flowering and capsule formation stage significantly improved the quality parameters, seed and stover yield, nutrient concentration, and uptake over control and could be used to alleviate the B, S, and N deficiency in Indian mustard.